Genotypic and environmental effects on quality and nutritional attributes of Moroccan barley cultivars and elite breeding lines - Elouadi, Fadwa; Amri, Ahmed; El-Baouchi, Adil; Kehel, Zakaria; Jilal, Abderrazek; Ibriz, Mohammed (Frontiers in Nutrition, 2023)
Barley, although used mainly for livestock feed and for beverages, its use as human feed can contribute to enrich human diets with some health benefits. The development of new hulless varieties rich in β-glucans and micro-nutrients can enhance the use of barley as food but little is known about the effects of the environment on these nutritional traits. In this study, we evaluated five Moroccan varieties and two elite breeding lines of barley at four locations in Morocco during 2016-17 and 2017-18 cropping seasons. The results showed highly significant differences between genotypes for β-glucan, protein, Iron and Selenium contents and for 1000 kernel weight but not for Zinc content; significant to highly significant differences between environments for all traits except for β-glucans content; and significant to highly significant interactions for all traits. The highest level of β-glucan content has reached 11.57% observed at Sidi El Aydi site during the growing season 2017-2018 for the hulless variety Chifaa., This variety has shown the highest content of β-glucan (6.2 to 11.57%) over all environments except at Tassaout during 2016-17 season. The breeding line M9V5 has achieved a significantly higher protein content at all the locations during the two growing seasons ranging from 12.38 to 20.14 %. Most hulless lines had significantly higher β-glucan and protein contents, but lower 1000 kernel weight. For micro-nutrients, the content ranges were 28.94 to 38.23 ppm for Fe, 28.78 to 36.49 ppm for Zn and 0.14 to 0.18 ppm for Se with the highest content for Fe and Zn shown by the breeding line M9V5 and Chifaa showed average contents of 33.39 ppm, 35.34 ppm and 0.18 ppm for Fe, Zn and Se, respectively. The GGE biplot confirmed the high and relatively stable content of β-glucan and acceptable micro-nutrients contents of Chifaa variety and identified Marchouch as the most discriminant site to breed for biofortified barley varieties.